ANALISIS KELAYAKAN USAHA UNIT PEMECAH BATU DENGAN PENDAKATAN “CAPITAL BUDGETING” PADA CV EKA MANDIRI RANDU ACIR SALATIGA - Afandi, Pandi (JURNAL STIE SEMARANG, 2014)
Blazed the way new Effort Elegibility and run to need the careful consideration, particularly if amount of invesment which provided very big and its rate of return require the time old ones by various risk which possible arise in its business environment. CV Eka Mandiri Randu Acir Salatiga plan to do open the knapping business unit of stone utilize the to fulfill of requirement of development material for roadwork, bridge, building, other infrastructure project and irrigation requiring meterial stone from various size measure. The effort besides requiring farm which enough wide of needing also the expense of big enough capital, so that to determine its elegibility is needed by analysis of elegibility finansial. Analyzer used is]" capital budgeting" provided with the analysis of payback period ( PBP), Net Present Value ( NPV), Profitability of Index ( PI) and Internal Rate Of Return ( IRR). Result of research indicate that the Payback Period obtained by result 4,5 quicker year from maximum period payback 10 year, Positive NPV 339.142.040, PI (profitability index) of equal to 1,207 bigger than number 1 and IRR of equal to 17,98 bigger than value of cost of capital 13,2 %, so that the project of knapping business unit of CV Eka Mandiri of Randu Acir Salatiga by finansial through the capital budgeting " Feasible and competent" to be run. Is hereinafter suggested for the follow up of result of this study by equiping other analysis  like social impact analysis, environmental impact and analyse the non other economics.